Punishment of Criminals of Trafficking in Persons: Legal Perspective on International Guidelines and Indonesian Practices - Farhana, Farhana (International Journal of Criminology and Sociology, 2021)
The background of this study is that penalization is not only oriented towards the perpetrators of crimes of trafficking in persons but also oriented to the interests of victims and the community so that criminal justice aims to integrally protect various interests. The study aims to identify the punishment of criminals of trafficking in persons based on the interests of victims in Indonesian court practices as outlined by some regulations and the international community as outlined by the United Nations Office on Drugs and Crime (UNODC) and United Nations Convention Against Transnational Organized Crime (UNTOC). Considering that the study is a transnational crime, the point of view used in this study is clear to analyse the perspective of the national community and the ‎international community. Hence, the standard ‎measuring instrument used the perspective of international justice and its practical implementation by the Indonesian court. By using the library research method, the results showed that trafficking crimes are considered serious crimes by the international community. In regulating human trafficking, every country has laws regarding trafficking crimes by the applicable legal system. The theoretical contribution of this study is that each human trafficking crime case has different characteristics due to the condition of the perpetrator, the victim, the situation when the trafficking crime was committed. Therefore, as a practical contribution, the Indonesian court considers these factors which can be considered as a weighting or a reduction in sentence. The problem is incriminating and mitigating factors that must be considered in imposing penalties against traffickers. The study offers originality in investigating the factors which are burdensome and mitigate in imposing crimes against traffickers. The findings underline the principle of criminalization as the basis for imposing penalties on perpetrators of trafficking in persons by taking into account the factors of weighting and mitigation of punishment, in which the proportional principle takes precedence in addition to the other principles.